Fluorescein sodium as a marker for focused ultrasound-induced blood-brain barrier disruption: a case report in a porcine model - Xu, Yuan; On, Thomas J.; Preul, Mark C. (Frontiers in Surgery, 2025)
Transcranial low-intensity focused ultrasound (FUS) enables noninvasive, targeted, and reversible blood-brain barrier (BBB) disruption, facilitating drug delivery and liquid biopsy of the brain. Using fluorescein sodium (FNa) with macroscopic widefield fluorescence and microscopic confocal laser endomicroscopy (CLE) imaging, we assessed BBB permeability after applying a frameless, electromagnetic-guided FUS system in a porcine model and confirmed with established MRI protocol and conventional histology. Both macroscopic and microscopic FNa fluorescence imaging findings correlated with contrast-enhanced MRI, providing direct evidence of BBB disruption. This approach demonstrates the utility of FNa for evaluating BBB permeability in preclinical studies.